How efficient are our partnership? PABRA after 25 years: Taking a critical look at its partnerships’ efficiency - Schuetz, Tonya; Poulos, Allison; Sharkey, Rowan; Rubyogo, Jean Claude; Onyango, Patricia (2024)
The Pan-African Bean Research Alliance (PABRA), established by CIAT in 1996, conducted a partnership efficiency survey after 25 years of operation across 31 sub-Saharan African countries with over 934 partners, including 432 farmer organizations. Two online surveys were administered—one to 140 PABRA partners and another to CIAT Bean Program team members—evaluating partnership efficiency across five areas: Vision, Leadership, Accountability, Communications & Dissemination, and Impact using a 1-5 Likert scale. Results showed broadly positive feedback with identified areas for improvement, particularly in communication, dissemination, and report sharing. Key enabling factors for successful partnerships included shared vision, government/NGO collaboration for farmer outreach, involvement of national programs as formal entry points, tailored dissemination products, private sector engagement, and collaborative relationships with technically capable partners. Main challenges identified were the need for constant engagement to ensure proper fund management, difficulty finding technically capable partners, and aligning funding cycles with cropping seasons. The survey results informed a team retreat focused on strengthening existing partnerships and exploring new opportunities. Next steps include continued analysis of the survey results, follow-up on specific partner suggestions, and enhanced capacity building through student programs and technical training opportunities to improve bean variety development and value chain efficiency across Africa.